RIG-I Detects Kaposi’s Sarcoma-Associated Herpesvirus Transcripts in a RNA Polymerase III-Independent Manner - Yugen Zhang (American Society for Microbiology, 2018)
ABSTRACT Retinoic acid-inducible gene I (RIG-I) is a cytosolic pathogen recognition receptor that initiates the innate immune response against many RNA viruses. We previously showed that RIG-I restricts Kaposi's sarcoma-associated herpesvirus (KSHV) reactivation (J. A. West et al., J Virol 88:5778–5787, 2014, https://doi.org/10.1128/JVI.03226-13). In this study, we report that KSHV stimulates the RIG-I signaling pathway in a RNA polymerase (Pol) III-independent manner and subsequently induces type I interferon (IFN) responses. Knockdown or inhibition of RNA Pol III had no effect on beta interferon (IFN-β) induction by KSHV. By using high-throughput sequencing of RNA isolated by cross-linking immunoprecipitation (HITS-CLIP) approach, we identified multiple KSHV regions that give rise to RNA fragments binding to RIG-I, such as ORF810420-10496, Repeat region (LIR1)119059-119204, and ORF2543561-43650. The sequence dissimilarity between these fragments suggests that RIG-I detects a particular structure rather than a specific sequence motif. Synthesized ORF810420-10496 RNA stimulated RIG-I-dependent but RNA Pol III-independent IFN-β signaling. In summary, several KSHV RNAs are sensed by RIG-I in a RNA Pol III-independent manner. IMPORTANCE Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi’s sarcoma, primary effusion lymphoma, and multicentric Castleman’s disease. Innate immune responses against viral infections, especially the induction of type I interferon, are critical for limiting the replication of viruses. Retinoic acid-inducible gene I (RIG-I), a cytosolic RNA helicase sensor, plays a significant role in the induction of type I interferon responses following viral infection. Here, we identified multiple RNA regions in KSHV as potential virus ligands that bind to RIG-I and stimulate RIG-I-dependent but RNA Pol III-independent IFN-β signaling. Our results expand the role of RIG-I by providing an example of a DNA virus activating a canonical RNA-sensing pathway.